2016
DOI: 10.3389/fpls.2016.01198
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Uptake and Allocation – A Closer Look at Arabidopsis thaliana L. and Oryza sativa L.

Abstract: This year marks the 20th anniversary of the discovery and characterization of the two Arabidopsis PHT1 genes encoding the phosphate transporter in Arabidopsis thaliana. So far, multiple inorganic phosphate (Pi) transporters have been described, and the molecular basis of Pi acquisition by plants has been well-characterized. These genes are involved in Pi acquisition, allocation, and/or signal transduction. This review summarizes how Pi is taken up by the roots and further distributed within two plants: A. thal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(73 citation statements)
references
References 206 publications
2
71
0
Order By: Relevance
“…Additionally, the plants tested in the previous study were younger and thus potentially at a different growth stage to the plants used in this study. Phosphate starvation triggers the mobilisation of phosphate from older leaves to sink organs (Młodzińska & Zboińska ), and it is possible that this mobile phosphate modulates the need for phosphate uptake. Signalling by root‐produced miR399* and miR399 to the shoots in older plants may occur as a result of this effect, in order to better communicate the need for phosphate uptake by the roots.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the plants tested in the previous study were younger and thus potentially at a different growth stage to the plants used in this study. Phosphate starvation triggers the mobilisation of phosphate from older leaves to sink organs (Młodzińska & Zboińska ), and it is possible that this mobile phosphate modulates the need for phosphate uptake. Signalling by root‐produced miR399* and miR399 to the shoots in older plants may occur as a result of this effect, in order to better communicate the need for phosphate uptake by the roots.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphate uptake and allocation are tightly regulated in plants with highly efficient Pi remobilization (Nagarajan et al, 2011;Nussaume et al, 2011). In rice, studies have shown that several PHT family transporters are involved in redistributing Pi from older leaves to younger tissues (Młodzińska and Zboińska, 2016). Further work should examine whether these PHT transporter genes are posttranscriptionally regulated by rice SR40 and SCL57.…”
Section: Sr Proteins Play Key Roles In Regulating Mineral Homeostasismentioning
confidence: 99%
“…Plants acquire phosphorus in the inorganic form (Pi) by high affinity transporters (PHTs) and Pi/H + symporters (Mlodzinska and Zboinska, 2016). In Arabidopsis , PHT gene family is divided into four groups (PHT1, PHT2, PHT3, and PHT4) are involved in different functions.…”
Section: Phosphorus (P)mentioning
confidence: 99%